2008
DOI: 10.1126/science.1154433
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal Dysfunction in Patients with Obsessive-Compulsive Disorder and Their Unaffected Relatives

Abstract: Obsessive-compulsive disorder (OCD) is characterized by repetitive thoughts and behaviors associated with underlying dysregulation of frontostriatal circuitry. Central to neurobiological models of OCD is the orbitofrontal cortex, a neural region that facilitates behavioral flexibility after negative feedback (reversal learning). We identified abnormally reduced activation of several cortical regions, including the lateral orbitofrontal cortex, during reversal learning in OCD patients and their clinically unaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
364
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(408 citation statements)
references
References 17 publications
31
364
1
5
Order By: Relevance
“…NJREs might also be considered (and investigated) as a putative marker for OCD, in the same way in which the construct Anxiety Sensitivity (AS) is deemed a psychological marker of anxiety disorders in general and panic disorder in particular (e.g., Brown, Smits, Powers, & Telch, 2003;Rapee & Medoro, 1994;Schmidt, Lerew, & Jackson, 1997;Smits, Powers, Cho, & Telch, 2004; see literature on endophenotypes, Chamberlain et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…NJREs might also be considered (and investigated) as a putative marker for OCD, in the same way in which the construct Anxiety Sensitivity (AS) is deemed a psychological marker of anxiety disorders in general and panic disorder in particular (e.g., Brown, Smits, Powers, & Telch, 2003;Rapee & Medoro, 1994;Schmidt, Lerew, & Jackson, 1997;Smits, Powers, Cho, & Telch, 2004; see literature on endophenotypes, Chamberlain et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The OFC is likely related to deficits of cognitive regulation of emotionally salient information. Accordingly, Chamberlain et al (2008)recently showed that, in comparison with HC, lateral OFC activation is reduced during a task that assesses behavioral flexibility in OCD patients and in unaffected relatives. These findings suggest that the lateral OFC could have a central function in cognitive flexibility deficits and, thus, in the genesis of pathological habits (Chamberlain et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…tDCS was chosen as it can modulate intrinsic neuronal activity using a weak, constant electrical current (Nitsche et al., 2008) to facilitate cognitive processing including learning and memory (Asthana et al., 2013; Coffman, Clark, & Parasuraman, 2014; Mungee et al., 2014). This work aligns with the rapidly growing body of research that indicates tDCS may have beneficial effects for psychiatric conditions associated with altered prefrontal activity or connectivity, including depression (Drevets, Price, & Furey, 2008), schizophrenia (Meyer‐Lindenberg et al., 2002), and obsessive–compulsive disorder (Chamberlain et al., 2008). For instance, recent studies have demonstrated tDCS to reduce severity of depression (Brunoni et al., 2013, 2016; Shiozawa et al., 2014) as well as promising results to reduce severity of symptoms associated with schizophrenia (Brunelin et al., 2012; Hoy, Arnold, Emonson, Daskalakis, & Fitzgerald, 2014).…”
Section: Introductionmentioning
confidence: 99%